China and Iran Economic, Political, and Military Relations - Harold, Scott (RAND Corporation, 2012)
The partnership between the Islamic Republic of Iran and the People's Republic of China presents a unique challenge to U.S. interests and objectives, including dissuading Iran from developing a nuclear weapons capability. This paper examines factors driving Chinese-Iranian cooperation, potential tensions in the Chinese-Iranian partnership, and U.S. policy options for influencing this partnership to meet U.S. objectives.